Purification of spent deicing fluid by membrane techniques - Joni Lehto (IWA Publishing, 2021)
Membrane-based concept comprising microfiltration and nanofiltration pre-treatments, reverse osmosis pre-concentration, and membrane distillation used for final concentration was applied for producing purified and concentrated recycled deicing fluid. Additionally, a techno-economic assessment was conducted to determine the economic viability of the recycling concept. By a straightforward membrane-based concept, ∼95% of solid and colloidal impurities together with certain deicing fluid additives such as colorants and surfactants could be efficiently removed (removal efficiencies of ∼90% and ∼93%, respectively), and resulting purified deicing fluid could be concentrated to ∼60 wt% glycol solution, enabling its recycling in deicing operations. Preliminary techno-economic assessment indicated that a membrane-based concept can be used as an economically viable alternative for recycling the spent deicing fluid at airports. The techno-economic case study at an airport consuming 4,000 tonnes of deicing fluid during 6 months annually showed the concept to be economically feasible when the price of purchased propylene glycol is over 1,000 EUR/tonne. In addition to the purchase price of the propylene glycol, the most important cost factors were labor cost and the annual consumption of deicing fluid. Integrating the membrane concept with other operations at airport has potential to decrease the labor cost and further improve the economic feasibility of the concept. HIGHLIGHTS Membrane concept was successfully utilized for purification and concentration of spent deicing fluid.; By the applied membrane concept, a glycol solution having ∼60 wt% of glycol could be produced.; Utilized concept was able to remove over 90% of impurities.; TEA indicated the concept to be economically feasible.; Integrating the operation of the concept with other operations at airport can potentially decrease the labor cost.;